Dermatoglyphic Assessment in Male Down Syndrome (Community Based Medical Journal, 2022)
Down syndrome (DS) is the most common chromosomal disorder which causes intellectual disability. It is mainly because of the presence of extra copy of chromosome number 21. Dermatoglyphic has been well established as a diagnostic aid in number of diseases having hereditary basis. Dermatoglyphic data was obtained by the use of ink and prints on a paper. This cross-sectional, analytical type of study was performed at the Department of Anatomy, Dhaka Medical College, Dhaka from January 2017 to December 2017 on 40 Down syndrome subjects (age ranged from 6 to 16) selected from Society for the Welfare of the Intellectually Disabled, Bangladesh (SWID, Bangladesh) and Down Syndrome Society of Bangladesh (DSS) and compared with 40 controls for the establishment of comparison between two groups. Dermatoglyphic prints were used to evaluate the difference in „atd‟ „dat‟ „adt‟ angles and pattern intensity between the control and the DS individuals. The results showed that „atd‟ angle was significantly higher (p